2010
DOI: 10.1177/0960327109357217
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcer role of herbomineral siddha drug — Thamira parpam on experimentally induced gastric mucosal damage in rats

Abstract: Anti-ulcerogenic activity of Thamira parpam (TP) was investigated in two ulcer models (aspirin + pylorus ligation and HCl-ethanol). Aspirin—pylorus ligation (Asp 200 mg/kg-7 days + PL-4 hours) and HCl-ethanol (150 mM HCl in 70% ethanol) induction in rat resulted in elevation of thiobarbituric acid reactive substances (TBARS) and depletion of antioxidants (superoxide dismutase [SOD], glutathione [GSH], glutathione peroxidase [GPx]) with high ulcer scores (p < .01). In Asp + PL model, TP treatment sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In the present study, ME and aqueous solution of TGF-α and/or aprotinin were used on the healing of duodenal ulcer induced by acidified ASA. Previous studies have demonstrated that reactive oxygen specimens are involved in ASA induced gastric mucosal damage due to an enhancing effect of lipid peroxidation and attenuation of mucosal antioxidant mechanisms [30,31]. In the present study, ulcer index and MDA levels were significantly elevated in the duodenal tissue after intragastrically acidified ASA aplication ( Figure 1, Figure 2).…”
Section: Discussionsupporting
confidence: 61%
“…In the present study, ME and aqueous solution of TGF-α and/or aprotinin were used on the healing of duodenal ulcer induced by acidified ASA. Previous studies have demonstrated that reactive oxygen specimens are involved in ASA induced gastric mucosal damage due to an enhancing effect of lipid peroxidation and attenuation of mucosal antioxidant mechanisms [30,31]. In the present study, ulcer index and MDA levels were significantly elevated in the duodenal tissue after intragastrically acidified ASA aplication ( Figure 1, Figure 2).…”
Section: Discussionsupporting
confidence: 61%
“…GSH is an endogenous antioxidant component and its activity is related to the thiol group of cysteine in its structure [24]. GSH reacts with peroxides and toxic oxygen radicals such as the hydroxyl ion and singlet oxygen to protect cells from injury [28]. In this study, administration of BCT exhibited a singfincant reduction in the MDA level, a lipid peroxidation product compared with the animals given ethanol (EtOH group).…”
Section: Discussionmentioning
confidence: 76%
“…TP is known as “Gunma kalan” in Siddha literature which means that the drug is effective in healing ulcers. The anti-ulcer efficacy of TP has already been reported in rats from our laboratory ( Parameswari et al, 2010 ; Vasanthkumar et al, 2010 ). The purified form of copper oxide is used in the treatment and management of obesity, tuberculosis, cough, asthma, skin diseases, and obesity ( Bhavyasree and Xavier, 2020 ).…”
Section: Introductionmentioning
confidence: 66%